RANTAI NILAI PERDAGANGAN PRODUK ORGANIK DAN DETERMINAN KEPUTUSAN KONSUMEN UNTUK MEMBELI - Yanuarita Hendrani; Sandra Sunanto; PC Suroso; Anna Farina Poerbonegoro (EKUITAS (Jurnal Ekonomi dan Keuangan), 2015)
The shift in consumption patterns from non-organic to organic products has hit many developed countries in the last two decades. This is supported by the increase in people's income, urbanization, awareness of environmental and health issues and changes in the demographic structure. For a developing country like Indonesia, shifting eating pattern such as that experienced by the developed countries actually has occurred especially among the middle to upper- income level. This study aims to analyze the value chain of production and distribution of organic products and their determinants of purchase. The results show that the distribution channels of organic products vary. Some farmers sell their products directly to consumers or supermarket, while others use agents to collect the products and sell them to the consumers, supermarkets or to other agents. The highest added value creation occurs in the upstream. From the ordered logit model applied, it can be concluded that there is a positive effect of income on the probability of buying organic products more frequently but there is no significant effect of education. The probability to buy organic products more frequently is also higher for younger ages, but the reason to consume related with the environment and a high price do not affect the probability to buy organic products.